The Appraisal Analysis of National Exam Issues: A Discourse Analysis - Nurhadi, Kardi (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2017)
Appraisal is a system of interpersonal meanings. Martin and Rose (2003:22) explain that the term of appraisal for negotiating our social relationship, by telling our listeners or readers how we feel about things and people (in a word, what our attitudes are). This article tries to analyse the appraisal meaning from the news article. The appraisal analysis using discourse analysis based on Martin and Rose work. Then, the analysis focus on how texts are produced as social practice and how texts represent as an ideology (power struggle). The text is taken from news article from The Jakarta Post. The issues took about national examination issues. The result of analysis show that, the writer found three basic of appraisal meaning namely attitude, amplification and source of the text. The attitude is divided into three parts namely affect (feelings), judgement (character) and appreciation (value). In national exams issues many people give their feeling, judgement and appreciation. By knowing the appraisal analysis we will know how texts are produced as social practice. Also, the national exam issues have an ideology (power struggle). The ideology consist of two parts namely perspective and bias. Perspective refers to how do the people give their opinion, while bias means how do the texts affect the people. Keywords : Appraisal, interpersonal meaning, social practice, ideology, perspective, bias